Legal Protection of Children as Victims of Sexual Exploitation - Fadhilah, Ina Nur; Panjaitan, Junifer Dame (Worldwide Research Publishing, 2024)
The government has accommodated children's rights in Law Number 39 of 1999 concerning Human Rights which is an umbrella act for all forms of human rights protection in Indonesia, including children's rights. Commercial Sexual Exploitation of Children (CSEC) in girls where girls are easily persuaded, is sold at a high selling value. Consumers assume that girls are cleaner from venereal diseases and not too many suffer from them. Children who are victims of CSEC are entitled to legal protection from law enforcement, the government and the state to ensure that children's rights remain unfulfilled. Normatively, the rights of CSEC victims are adequately protected by Law Number 23 of 2002 concerning Child Protection (Articles 4-20). In this case, the protection of children's rights has acquired a stronger legal basis, because in more detail the rights and obligations of the child's executors have been regulated in such a way, including their criminal provisions. Children of CSEC victims receive special protection through Article 59 and Article 64 paragraph (3) of Law No. 23/2002. In addition to Article 5 of Law Number 13 of 2006 concerning the Protection of Witnesses and Victims